Water Purification in Atmospheric Water Generator - Sayed Ali; Wahid Ali; Kareem Hamad (Port Said Engineering Research Journal, 2022)
Atmospheric Water Generator (AWG) is a machine that could save the Earth from running out of fresh water in the future. This machine extracts clean water from humid air using power source to decrease the air temperature to its dew point. Consequently, the water vapor will be condensed and collected. The collected water has to be treated to satisfy the standards of drinking water. In this paper, the water treatment is configured using different processes. The verification is achieved via simulation for mineral treatment process. While the validation is performed by experimental work for other processes. The results affirmed that the generated water is potable and satisfy the market needs according to the Egyptian standards. These results are also consistent with World Health Organization standards (WHO). In this research we have tried several methods for purification including manual mineral addition and using mineral filters, not only that but also disinfection of water has been achieved using ultraviolet.